PENGARUH KEMAMPUAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR KECAMATAN SAMPANG KABUPATEN SAMPANG YANG DIMEDIASI OLEH MOTIVASI - Dwi Budiyatno; Subijanto; Woro Utari (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
Dwi Budiyatno, 2022. The Effect of Work Ability on Employee Performance at the Sampang District Office, Sampang Regency Mediated by Motivation, Postgraduate Program at Wijaya Putra University. This type of research is explanatory, namely to test hypotheses between hypothesized variables that will be tested for truth. by using a quantitative approach, the research sample was 94 respondents. In this study, the data will be processed using SEM-PLS data analysis. The aims of this research are: 1). To determine the significant effect of work ability on employee performance. 2). To determine the significant effect of work ability on employee motivation. 3). To determine the significant effect of motivation on employee performance. 4). To determine the significant effect of work ability on employee performance mediated by motivation. The results showed that: 1). Work ability has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.436 and the p-values ​​of 0.000. 2). work ability has a positive and significant effect on motivation. This is evidenced by the original sample value of 0.358 and the p-values ​​of 0.002. 5). Motivation has a positive and significant effect on employee performance. This is evidenced by the original sample value of 0.502 and the p-values ​​of 0.000. 6). Work ability has a significant positive effect on employee performance mediated by motivation. This is evidenced by the original sample value of 0.179 and p-values ​​of 0.022.